Distinct effect of stress on 11beta-hydroxysteroid dehydrogenase type 1 and corticosteroid receptors in dorsal and ventral hippocampus - Ergang, Peter; Kuželová, A; Soták, Matúš; Klusoňová, Petra; Makal, J; Pácha, Jiří (Physiological research, 2014)
Multiple lines of evidence suggest the participation of the hippocampus in the feedback inhibition of the hypothalamus-pituitary-adrenal axis during stress response. This inhibition is mediated by glucocorticoid feedback due to the sensitivity of the hippocampus to these hormones. The sensitivity is determined by the expression of glucocorticoid (GR) and mineralocorticoid (MR) receptors and 11beta-hydroxysteroid dehydrogenase type 1 (11HSD1), an enzyme that regulates the conversion of glucocorticoids from inactive to active form. The goal of our study was to assess the effect of stress on the expression of 11HSD1, GR and MR in the ventral and dorsal region of the CA1 hippocampus in three different rat strains with diverse responses to stress: Fisher 344, Lewis and Wistar. Stress stimulated 11HSD1 in the ventral but not dorsal CA1 hippocampus of Fisher 344 but not Lewis or Wistar rats. In contrast, GR expression following stress was decreased in the dorsal but not ventral CA1 hippocampus of all three strains. MR expression was not changed in either the dorsal or ventral CA1 region. These results indicate that (1) depending on the strain, stress stimulates 11HSD1 in the ventral hippocampus, which is known to be involved in stress and emotion reactions whereas (2) independent of strain, stress inhibits GR in the dorsal hippocampus, which is predominantly involved in cognitive functions.
Keywords: Animals; potkani inbrední LEW; hipokampus; 11-beta-hydroxysteroiddehydrogenasa typ 1; Rats, Wistar; psychický stres; druhová specificita; Rats, Inbred F344; Species Specificity; Male; Receptors, Steroid; Stress, Psychological; 11-beta-Hydroxysteroid Dehydrogenase Type 1; potkani inbrední F344; krysa rodu Rattus; Hippocampus; mužské pohlaví; zvířata; Rats, Inbred Lew; Rats; potkani Wistar; steroidní receptory